Komunikasi Gambar Bercerita pada Buku Belajar Baca Anak Taman Kanak-Kanak - Priyanto Sunarto; Pindi Setiawan (Journal of Visual Art and Design, 2013)
Visual communication experience that ensues between the picture and the children is an episode that should be experienced long before kindergarten children learn to read. Each visual element in the picture has a causal link that connects to an event.  Joint visual communication experience illustrates visual language strength in delivering messages actively or when they work together.  This experience provides an opportunity for the picture to send messages actively and get children accustomed to get the message and tell the message from the picture they gazed at. This research discussed the importance of storytelling pictures in visual communication experience with children. This research results' are three models of communications between picture and all visual elements and the working method of those models, based on children visual-word language indicators. The dynamics in this communication model show how far the role of child assistants (parents and teachers) in motivating and facilitating the occurence of interaction between the picture and the child independently. This research verified the importance of child activity for gazing the picture which should be executed before the child is able to read letters. This study also illustrated the importance of two key functions of storytelling pictures as an active messenger by gazing the picture and a letter interpreter for learning how to read.